Cerita Rakyat Masyarakat Rambah Kabaputen Rokan Hulu Provinsi Riau - M . Firdaus; Hasnah Faizah; Ngusman Abdul Manaf (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: Position and function of oral literature including folklore is increasingly displaced due to technological advances, cultural systems, social systems, and political systems are developed. Therefore, efforts should be made documenting folklore Rambah society. The purpose of this study was to describe the categories, structure and social functions contained in the folklore society Rambah. This study used a qualitative approach with descriptive methods. Object of this study is the folklore society Sand Pengaraian Rambah district. Data collection was done by recording, recording and interviews. Then proceed to describe and interpret the results. Data analysis was performed through a data inventory phase, phase of data analysis, and reporting phases. Based on the research and discussion of public folklore Rambah divided into three categories, namely fairy tales, legends, and myths. Of the fourteen stories, stories that have category found eight legends, myths category four stories, and a bit of a fairy tale by the two stories. In terms of structure, folklore Rambah people are more likely to use the plot forward and a third person perspective. Moreover, in terms of style more common stylistic comparison, repetition, and contradiction. Rambah folklore society serves as a means of entertainment, education, faith bequeathed the means, the means to preserve the customs, culture, and traditions, shows Rambah community identity, as well as a means of fostering a spirit of togetherness. The results could be implicated in the Indonesian language learning with understanding the competency standard spoken folklore. Keywords: Cerita Rakyat, Masyarakat Rambah